A Low-Cost Electrochemical Cell Sensor Based on MWCNT-COOH/α-Fe2O3 for Toxicity Detection of Drinking Water Disinfection Byproducts - Ying Liu; Zhipeng Zhang; Yuling Wu; Huan Yang; Jiao Qu; Xiaolin Zhu (Nanomaterials)
The disinfection of drinking water is essential for eliminating pathogens and preventing waterborne diseases. However, this process generates various disinfection byproducts (DBPs), which toxicological research indicates can have detrimental effects on living organisms. Moreover, the safety of these DBPs has not been sufficiently assessed, underscoring the need for a comprehensive evaluation of their toxic effects and associated health risks. Compared to traditional methods for studying the toxicity of pollutants, emerging electrochemical sensing technologies offer advantages such as simplicity, speed, and sensitivity, presenting an effective means for toxicity research on pollutants. However, challenges remain in this field, including the need to improve electrode sensitivity and reduce electrode costs. In this study, a pencil graphite electrode (PGE) was modified with carboxylated multi-walled carbon nanotubes (MWCNT-COOH) and nano-iron (III) oxide (α-Fe2O3) to fabricate a low-cost electrode with excellent electrocatalytic performance for cell-active substances. Subsequently, a novel cellular electrochemical sensor was constructed for the sensitive detection of the toxicity of three drinking water DBPs. The half inhibitory concentration (IC50) values of 2-chlorophenylacetonitrile (2-CPAN), 3-chlorophenylacetonitrile (3-CPAN), and 4-chlorophenylacetonitrile (4-CPAN) for HepG2 cells were 660.69, 831.76, and 812.83 µM, respectively. This study provides technical support and scientific evidence for the toxicity detection and safety assessment of emerging contaminants.